(3LhGgQ GdCNHGQ hedM GdCNHGQs - (3CHh eMeO GdMSf Hf eMeO Hf CHj YbGeI Gdjefj,J (B480 (3g` s
(3ChdgG (B:s
(3bGd GdbGVi GdCLd GdMSf Hf eMeO Hf CHj YbGeI , GdMeO ddg Ydi fYeg GdJi dG JMUi HMSGH , hUdhGJg Ydi fHjg GdeQSd HCTQa cJGH , hYdi Bdg GdeWgQjf s
(3BNQgG (B:s
(3jbhdhf QHfG BefG aGZaQ dfG hCQMefG hCfJ NjQ GdQGMejf Edi bhdg (B: (3hGfce YdjfG dGJQLhYhf JeJ HMeO Gddg hefg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3cJHJ GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs